Synthesis and Characterization of Novel UV-Curable Waterborne Fluorinated Polyurethane Acrylate Latex - Liang1, Hongbo; Lv1, Cheng; Xiong1, Lei; Huang1, Shengmei; Fan1, Hongqing (Asian Journal of Chemistry, 2014)
In this study, a novel UV-curable waterborne fluorinated polyurethane acrylate (FPUA) latex was obtained from urethane acrylate with fluorinated acrylate copolymer prepared by free radical copolymerization. FT-IR analysis demonstrated that the fluorinated acrylate monomer had been introduced into the chain of the fluorinated polyurethane acrylate. XPS analysis showed that the atomic percent of fluorine on the air-film interface of fluorinated polyurethane acrylate films was much higher than that at the film-glass interface and this feature became more evident after heat treatment. In addition to, the effect of fluorinated monomers content on properties of the films was studied. The results showed that the hydrophobic/oleophobic properties and abrasion resistance of films were enhanced with the increase of fluorinated monomer content.